PENGARUH METODE SIRKUIT TRAINING TERHADAP HASIL SPRINT 60 METER SMP NEGERI 21 TERPADU PONTIANAK - Budiman, Budiman; Purnomo, Edi; Triansyah, Andika (Universitas Tanjungpura, 2022)
AbstractThis study aims to see the effect of the training circuit method on the results of the 60 meter sprint at SMP Negeri 21 Terpadu Pontianak. The method used in this study is a free experiment involving two variables of the training circuit method using the 60 meter sprint method. The sample of students and female students who took part in the extracurricular training at SMP Negeri 21 Terpadu Pontianak sports 60 meter running number consisting of 20 students. The research technique used tests and measurements. The results of this study indicate the effect of circuit training on the results of the 60 meter sprint on extracurricular students at SMP Negeri 21 Terpadu Pontianak. This can be proven based on the calculation results, where the ttest value is 5.869 the t table value (1.729), so the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. This shows that the Circuit Training method has an influence on the results of the 60 meter sprint at SMP Negeri 21 Terpadu Pontianak.Keywords: Circuit Training, Sprint 60 Meter, SMP Negeri 21 Terpadu Pontianak